2019
DOI: 10.15354/bece.19.ar1036
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Support, Reading Strategy and Reading Literacy: A Two-Level Mediation Model

Abstract: This study used a large-scale random sampling survey data called Regional Assessment of Education Quality (RAEQ) organized by Collaborative Innovation Center of Assessment toward Basic Education Quality in 2014. The school bullying phenomenon is described from the perspective of middle school students who were bullied. Regression is used to estimate the effects of academic achievement, self-esteem, interpersonal relationship and pro-social behavior on the different types of school bullying. And the differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In many previous studies that evaluated the PISA data, it was found that the teacher support had a positive effect on the reading performance (Radulovic et al, 2022;Chang & Bangsri, 2020;Chen et al, 2019;Ma et al, 2021;Mercer, 2011). While the perceived teacher support of Chinese students who participated in the PISA 2018 had a 5% effect on the reading literacy performance (Ma et al, 2021), it was a surprising finding that the teacher support did not contribute to the reading performance according to the perception of students from Türkiye (1‰).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In many previous studies that evaluated the PISA data, it was found that the teacher support had a positive effect on the reading performance (Radulovic et al, 2022;Chang & Bangsri, 2020;Chen et al, 2019;Ma et al, 2021;Mercer, 2011). While the perceived teacher support of Chinese students who participated in the PISA 2018 had a 5% effect on the reading literacy performance (Ma et al, 2021), it was a surprising finding that the teacher support did not contribute to the reading performance according to the perception of students from Türkiye (1‰).…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies demonstrated the relationship of teacher support with reading literacy (İnci & Kaya, 2022;Büyükatak 2022;Radulovic et al, 2022;Chang & Bangsri, 2020;Chen et al, 2019;Ma et al, 2021;Mercer, 2011), first reading (Silinskas et al ., 2016), participation in reading (Zhao et al, 2018;Berman-Young, 2014), academic achievements other than reading (Bal, 2011;Chen, 2017;Klem & Connell, 2014;Ma et al, 2017), academic feelings (Lei et al, 2018), and attitude towards school (Ertem et al, 2021) from various perspectives.…”
Section: Motivation Sources For Reading and Teacher Supportmentioning
confidence: 97%